4D Marine Cadastre Data Models – Turkey & Malaysia - H. Gürsoy Sürmeneli; A. Abdul Rahman; M. Alkan; A. Zamzuri; M. I. Hassan (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
In recent years, the demand for data has surged as the importance of sustainability has grown. Both academic and institutional efforts are being made to enhance the efficiency and sustainability of underground, surface, and marine resources. Data management models developed to marine these resources must be capable of operating independently or in an integrated manner. Physical data and legal rights must be represented and managed effectively to manage land and marine areas. Ultimately, it has become inevitable for existing cadastral systems to be improved and advanced into 3D/4D cadastral systems, particularly in land management. While LADM, an ISO standard, plays a key role in modelling legal rights, GIS-based standards (such as OpenGIS, CityGML, IFC, and InfraGML) have emerged for modelling physical data. It develops a more comprehensive land management system, and the modelling of rights related to planning, valuation, and marine areas is being explored in the second version of LADM (Sürmeneli et al., 2022; Zamzuri et al., 2021). In this study, marine cadastre was chosen as one of the key and impactful areas of cadastral work in recent years. The marine cadastre facilitates controlling and managing spatial information related to marine rights, including legal authorities' rights, restrictions, and responsibilities (RRRs) within the marine environment. It also primarily defines marine parcels. The functions of the marine cadastre and the definition of marine parcels should be developed following the cadastral systems of individual countries and relevant international standards (Zamzuri et al., 2022). This study, a collaborative effort, aims to identify the needs of a marine cadastre and to develop a data model based on the LADM standard. The paper is divided into two main sections: the design of data models for Malaysia and Turkey, and the development of corresponding data model schemas. The developed model is expected to facilitate a smooth integration process into existing cadastral systems, a result of the collective efforts of the research community. Initially, studies related to marine cadastre will be discussed, and information will be provided within the framework of international standards on which these studies are based. Next, the specific needs of Turkey and Malaysia will be outlined, reflecting the diverse perspectives and shared responsibilities in the field. After analysing the data model applications, the systems designed by both countries will be presented in sequence. The final output of the study will be a combined 4D (3D + Temporal) data model for land and marine cadastres, represented through UML diagrams. The study will conclude with the presentation of results and discussions, a testament to the collaborative nature of research in this field.